Low-Dose Growth Hormone is Cardioprotective in Uremia - Rabkin, Ralph (American Society of Nephrology, 2008)
Growth hormone (GH) is required to maintain normal cardiac structure and function and has a positive effect on cardiac remodeling in experimental and possibly human disease. Cardiac resistance to GH develops in the uremic state, perhaps predisposing to the characteristic cardiomyopathy associated with uremia. It was hypothesized that administration of low-dosage GH may have a salutary effect on the cardiac remodeling process in uremia, but because high levels of GH have adverse cardiac effects, administration of high-dosage GH may worsen uremic cardiomyopathy. In rats with chronic renal failure, quantitative cardiac morphology revealed a decrease in total capillary length and capillary length density and an increase in mean intercapillary distance and fibroblast volume density evident. Low-dosage GH prevented these changes. Collagen and TGF-β immunostaining, increased in chronic renal failure, were also reduced by GH, suggesting a mechanism for its salutary action. Low-dosage GH also prevented thickening of the carotid artery but did not affect aortic pathology. In contrast, high-dosage GH worsened several of these variables. These results suggest that low-dosage GH may benefit the heart and possibly the carotid arteries in chronic renal failure.